Hepatocellular Injury in Children Treated for Rifampicin-resistant Tuberculosis: Incidence, Etiology and Outcome. Issue 12 (6th September 2022) - Duvenhage, Joanie; Draper, Heather R.; Garcia-Prats, Anthony J.; Winckler, Jana; Hesseling, Anneke C.; Schaaf, H. Simon
Abstract : Background: Hepatocellular injury has been reported commonly in adults on rifampicin-resistant and multidrug-resistant tuberculosis (RR/MDR-TB) treatment. However, there are limited data in children. Methods: Two pharmacokinetic studies of children (0–17 years) routinely treated for RR/MDR-TB were conducted in Cape Town, South Africa between October 2011 and February 2020. Hepatocellular injury adverse events (AEs; defined as elevated alanine aminotransferase [ALT]) were documented serially. Data were analyzed to determine the incidence, etiology, risk factors, management and outcome of ALT elevation. Results: A total of 217 children, median age 3.6 years (interquartile range, 1.7–7.1 years) at enrollment were included. The median follow-up time was 14.0 months (interquartile range, 9.8–17.2 months). Fifty-five (25.3%) patients developed an ALT AE. Of these, 43 of 55 (78%) patients had 54 ALT AEs attributed to their RR/MDR-TB treatment. The incidence rate of ALT AEs related to RR-TB treatment was 22.4 per 100 person-years. Positive HIV status and having an elevated ALT at enrollment were associated with time to ALT AE attributed to RR/MDR-TB treatment, with P values 0.0427 and P < 0.0001, respectively. Hepatitis A IgM was positive in 11 of 14 (78.6%) severe (grade ≥3) cases of ALT AEs. In 8 of 14 (57%) severe ALT AEs, hepatotoxic drugs were stopped or temporarily interrupted. None had a fatal or unresolved outcome. Conclusions: Hepatocellular injury in children on RR/MDR-TB treatment is common, although usually mild; having elevated ALT early in treatment and HIV-positive status are possible risk factors. Hepatitis A was a common etiology of severe ALT AE in children treated for RR/MDR-TB.